1977
DOI: 10.1111/j.1432-1033.1977.tb11655.x
|View full text |Cite
|
Sign up to set email alerts
|

X‐Ray Investigation of the Binding of 1,10‐Phenanthroline and Imidazole to Horse‐Liver Alcohol Dehydrogenase

Abstract: We have studied the binding of two inhibitor molecules, imidazole and 1 ,lo-phenanthroline, to liver alcohol dehydrogenase by crystallographic methods. X-ray data for the imidazole complex were collected to 0.29-nm resolution and for the 1,lO-phenanthroline complex to 0.45-nm resolution. In both cases we found only one peak in the difference electron density maps close to the active zinc atom. The peak corresponding to 1,lO-phenanthroline overlaps the site of the density of the zinc-bound water in the apoenzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 41 publications
(11 reference statements)
2
55
0
Order By: Relevance
“…Spectroscopic studies of cadmium, copper, or cobalt substituted alcohol dehydrogenase in several instances have been taken to provide evidence for the presence of a fivecoordinated catalytic metal site [18][19][20]. The present results indicate that, to the extent that five-coordinate complexes do form with metal-substituted enzyme, this is likely to reflect the disparity in coordination preferences of different metal ions and cannot be taken to suggest that the catalytic metal site in native enzyme is five-coordinate.…”
Section: Comparison With Experimentsmentioning
confidence: 59%
See 1 more Smart Citation
“…Spectroscopic studies of cadmium, copper, or cobalt substituted alcohol dehydrogenase in several instances have been taken to provide evidence for the presence of a fivecoordinated catalytic metal site [18][19][20]. The present results indicate that, to the extent that five-coordinate complexes do form with metal-substituted enzyme, this is likely to reflect the disparity in coordination preferences of different metal ions and cannot be taken to suggest that the catalytic metal site in native enzyme is five-coordinate.…”
Section: Comparison With Experimentsmentioning
confidence: 59%
“…On the other hand, there is also strong crystallographic and spectroscopic evidence showing that binding to zinc of certain bidentate inhibitors is fivecoordinate [18][19][20]. Furthermore, spectroscopic studies of metal-substituted alcohol dehydrogenase have indicated that several binary and ternary complexes may be fivecoordinate [11][12][13][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies on model complexes have indicated that one of the cysteine sulfurs may be involved in non-covalent interactions with the substrate, and that this interaction causes a change of the S-metal-S angle (Shoner et al, 1995). (Boiwe and BrandCn, 1977) open (this work) closed (Eklund et al, 1982b) n. m. closed (Plapp et al, 1978) closed (Ramaswamy et al, 1994) n. m. open (CedergrenZeppezauer, 1983) closed (unpublished results) closed (Al-Karadaghi et al, 1994) flexible rigid rigid rigid Deprotonation of alcohol is usually assumed to occur prior to hydride transfer to the coenzyme (Pocker et al, 1986;Kvassman and Pettersson 1987). Thereby, the substrate will coordinate as an alkoxide ion and we suggest that the local structural change in the metal coordination geometry actually occurs during catalysis.…”
Section: Fractionmentioning
confidence: 99%
“…When a binary inhibitor complex is formed, in which the Zn-bound water has been exchanged for another ligand like imidazole, pyrazole or phenanthroline, no large structural changes are observed (Boiwe and BrandCn, 1977;Eklund et al, 1982b). Thus, exchange of the zinc-bound water with other small molecules seems to maintain the protein in the open conformation (orthorhombic crystals, space group C222,).…”
mentioning
confidence: 99%
“…Crystallographic and spectroscopic data showing that binding to zinc of certain bidentate inhibitors is fivecoordinate 14,15 have been taken as evidence in favor of these suggestions. Furthermore, spectroscopic studies of metal-substituted alcohol dehydrogenase have indicated that several binary and ternary complexes may be five-coordinate [6][7][8][15][16][17][18][19][20] , although other spectroscopic investigations contradict these results [21][22][23][24][25] .…”
Section: Introductionmentioning
confidence: 99%